2008
DOI: 10.1051/0004-6361:20078678
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field structures of galaxies derived from analysis of Faraday rotation measures, and perspectives for the SKA

Abstract: Context. The forthcoming new-generation radio telescope SKA (Square Kilometre Array) and its precursors will provide a rapidly growing number of polarized radio sources. Aims. Our analysis looks at what can be learned from these sources concerning the structure and evolution of magnetic fields of external galaxies. Methods. Recognition of magnetic structures is possible from Faraday rotation measures (RM) towards background sources behind galaxies or a continuous RM map obtained from the diffuse polarized emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 29 publications
2
106
0
1
Order By: Relevance
“…Our best-fit model of the large-scale field seems to resemble most closely the quadrisymmetric (QSS) spiral model illustrated, e.g., in Fig. 2 of Stepanov et al (2008). How a field with such a configuration, i.e., with many reversals, is formed is a question that still needs to be answered, in spite of the general opinion that a dynamo is involved.…”
Section: Summary and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our best-fit model of the large-scale field seems to resemble most closely the quadrisymmetric (QSS) spiral model illustrated, e.g., in Fig. 2 of Stepanov et al (2008). How a field with such a configuration, i.e., with many reversals, is formed is a question that still needs to be answered, in spite of the general opinion that a dynamo is involved.…”
Section: Summary and Discussionmentioning
confidence: 62%
“…In addition, the reversals that are observed seem to have a different character from those in the Galaxy (see, e.g., Beck 2009). However, only future studies of the distribution of rotation measures of extragalactic background sources observed through the disk of inclined nearby, well-resolved spiral galaxies, as discussed e.g., by Stepanov et al (2008), can tell whether the Galaxy is indeed exceptional as far as the large-scale magnetic field is concerned.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…3.2.2, but with an uncertainty drawn from a Gaussian with σ noise = 6.0 rad m −2 . This should be a reliable approximation of the maximum uncertainty in Faraday depth for a polarized signal with a S /N > 5 (Stepanov et al 2008). The results are shown in Fig.…”
Section: Australian Square Kilometre Array Pathfindermentioning
confidence: 83%
“…We select the HBA region of the spectrum with less contamination from radio frequency interference (120-160 MHz; Offringa et al 2013). In this frequency range, the uncertainty on Faraday depth values is expected to be ≤0.05 rad m −2 for a signal-to-noise ratio larger than 5 (Stepanov et al 2008). Ionospheric Faraday rotation can degrade the results at LOFAR frequencies; the same holds for SKA1 -band 1 observations; see the next section.…”
Section: Low-frequency Arraymentioning
confidence: 99%
“…Weak regular magnetic fields can also be measured by their Faraday rotation of polarized emission from background sources, but also requires deep integrations to obtain a sufficiently large number of sources (Stepanov et al 2008). The observations presented in this paper detected only one source behind the inner disk of IC 342 and another three behind the outer disk (see Sect.…”
Section: Magnetic Field Extentmentioning
confidence: 95%